Vivências de mulheres mães após diagnóstico de malformação fetal e a experiência vivida pela equipe de saúde - Zampoli, Ana Cláudia Monzon (2022)
Receiving the diagnosis of fetal malformation may contribute to significant bio psychosocial changes in the life of women and their support network. A factor that significantly interferes in these experiences is the care provided by the maternal and child health care team. The aim of this study was to understand how women in the border area experience the diagnosis of fetal malformation and the experience lived by the health team. This is a qualitative research based on the theoretical and methodological framework of Alfred Schütz’s Social Phenomenology. For data collection, interviews with a semi-structured script were used based on the Snowball technique or selected from the records available in the respective institutions where the mothers were assisted. The collection was conducted with the help of six mothers, who were diagnosed with congenital malformation in their pregnancies, and a multidisciplinary team: three doctors/obstetricians, three nurses, a psychologist and a geneticist biologist, all involved in maternal and child care in the municipalities of Foz do Iguaçu, in health services linked to the Municipal Health Department at the 9th Regional Health Department, in the city of Cascavel, in health services linked to the Municipal Health Department of the 10th Regional Health Department, in the University Hospital of Western Paraná and in the Center for Attention and Research in Facial Skull Anomalies. The results of the research on mothers of children with malformation were divided into five categories, in which three refer to the "reasons why": Receiving the diagnosis of congenital malformation; Experiencing pregnancy in the context of the support network and therapeutic itinerary and Becoming a mother of a child with malformation. The two following categories are the "reasons for": Expectations of care towards the social support network and Expectations of care towards the health network. In the research with the health professionals, the results related to the "reasons why" were three categories: The multiprofessional care, The communication of the diagnosis of fetal malformation and The facilitating and complicating aspects in the daily care. Meanwhile, the "reasons for" pointed out the expectations of these professionals towards the category identified as the Expansion of care and care networks. Through social phenomenology it was possible to identify the importance of the relationship built, from the light-hard care technology, between the health professional and the mother of children with malformation. However, the two audiences reported the difficulties faced in daily life and the expectation of improvement in the face of more humanized care, highlighting the lack of professional preparation for this type of relationship and the necessary improvements in public policies in the region. It is also necessary to look at the mother’s social support network, which contributes significantly to the experience and to coping with the diagnosis of malformation of her child and helps adjusting the care provided throughout the their life.